2022
DOI: 10.1308/rcsann.2021.0225
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strap muscle transection on voice and swallowing changes after thyroidectomy in patients without laryngeal nerve injury

Abstract: Introduction Voice and swallowing symptoms are frequently reported after thyroidectomy even without laryngeal nerve injury. We aimed to evaluate the effect of strap muscle transection on voice and swallowing outcome after thyroidectomy. Methods Group 1 (G1) consisted of 17 patients who had their strap muscles transected during thyroidectomy and group 2 (G2) consisted of 17 patients who had their strap muscles preserved during thyroidectomy. None of the patients had laryngeal nerve injury. Voice impairment scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…A Kocher incision, ligation of the superior and inferior vascular peduncles, and digital dissection remain the standard surgical steps, but resection of the pre-laryngeal musculature is often necessary for delivering large goiters. A 2022 study has for the first time evaluated its consequences on vocal and swallowing function: by using patient-reported impairment scores, a prospective head-to-head study of 34 patients revealed no significant differences when strap muscles are transected or not 55 .…”
Section: Indications and Classical Surgical Approaches To Rgmentioning
confidence: 99%
“…A Kocher incision, ligation of the superior and inferior vascular peduncles, and digital dissection remain the standard surgical steps, but resection of the pre-laryngeal musculature is often necessary for delivering large goiters. A 2022 study has for the first time evaluated its consequences on vocal and swallowing function: by using patient-reported impairment scores, a prospective head-to-head study of 34 patients revealed no significant differences when strap muscles are transected or not 55 .…”
Section: Indications and Classical Surgical Approaches To Rgmentioning
confidence: 99%